The Experience of Depression: A Qualitative Study of Adolescents With Depression Entering Psychotherapy. (12th May 2016) - Weitkamp, Katharina; Klein, Eva; Midgley, Nick
There is a lack of research in health psychology on the subjective experience of adolescents with mental health disorders. The aim of this study was to explore the experience of depression and the journey into therapy of young people (YP) diagnosed with depression. Semi-structured interviews were carried out with six YP (5 female, aged 15–19). Interviews were analyzed using Interpretative Phenomenological Analysis. The following four key themes were identified: "Suffering is experienced as overwhelming, " "An experience of loneliness and isolation, " "Struggling to understand the suffering, " and "Therapy as a last resort." Reasons for a delay in accessing treatment were not knowing what is "normal, " the feeling that they have to deal with it by themselves, and/or the lack of a caring adult who supports the YP in getting help. The findings suggest the ongoing importance of reducing stigma and promoting mental health education for YP as well as parents, school staff, and health professionals.